2020
DOI: 10.1099/acmi.0.000076
|View full text |Cite
|
Sign up to set email alerts
|

Rare case report of infective endocarditis due to Kocuria kristinae in a patient with ventricular septal defect

Abstract: Background. Infective endocarditis (IE) is an uncommon but life-threatening infection. It is commonly associated with diseased or damaged valves. Patients with congenital heart disease are more prone to getting IE than the general population. The typical organisms that cause IE include Staphylococcus , Coagulase-negative Staphylococcus, Streptococcus viridians and Enterococci. However, the importance of rare micro-organisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The newest case report by Arif et al reported a rare case of right-sided IE due to K. kristinae presenting with undiagnosed fever for 1 year. 6 In our case, the patient also had a history of prolonged fever that increase suspicion for K. kristinae infection. IE is a possible cause of a prolonged fever, especially in the presence of congenital heart disease.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The newest case report by Arif et al reported a rare case of right-sided IE due to K. kristinae presenting with undiagnosed fever for 1 year. 6 In our case, the patient also had a history of prolonged fever that increase suspicion for K. kristinae infection. IE is a possible cause of a prolonged fever, especially in the presence of congenital heart disease.…”
Section: Discussionmentioning
confidence: 63%
“…koji su opisali rijedak slučaj IE-a na desnoj strani srca zbog infekcije bakterijama K. kristinae koja se manifestirala kao nedijagnosticirana povišena temperatura u trajanju od 1 godine. 6 U našem je slučaju bolesnica također imala anamnestičke podatke o dugotrajnoj povišenoj temperaturi, što povećava sumnju na infekciju čiji je uzročnik bila K. kristinae. IE je mogući uzrok dugotrajno povišene temperature, pogotovo uz prisutnost prirođene bolesti srca.…”
Section: Raspravaunclassified
“…22 In addition, it might be underestimated considering their close similarity to coagulase negative Staphylococci. 7,23 The automated diagnosis by the Vitek 2 database allows for better identification of Kocuria in the recent times. 13 mainly in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis (IE) presents a myriad of clinical features that depend on the causative organism, its virulence, duration of bacteremia, and presence of implantable cardiac devices [ 1 ]. Adding to this clinical complexity, any microorganism is known to cause IE, as described in various case reports [ 2 , 3 ]. Considering these evolving clinical findings, there is a concern for the delay in diagnosis leading to worse outcomes.…”
Section: Introductionmentioning
confidence: 99%